2008
DOI: 10.1017/s0265051707007747
|View full text |Cite
|
Sign up to set email alerts
|

Creating a musical world in the classroom: application of a Bourdieuan approach towards understanding teacher practice

Abstract: Whilst a rationale for the content and organisation of knowledge in a standardised curriculum may be clearly articulated at official policy level, factors may come to bear on a teacher operating at a local level which may work against the successful implementation of the curriculum on the ground. Drawing on a Bourdieuan notion of cultural field, ‘habitus’ and cultural capital to examine commonality and difference in teacher practice in an Irish primary school context, the paper reports on a study which highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This need has been widely reported in research studies over many years, such as by Mills (1989), Hennessy (2000), Stunell (2006) and McCulloough (2006) in England, Stakelum (2008) in Ireland, Ballantyne (2007), Barton (2015) and Jeanneret (1997) in Australia, Bresler (1993) in the USA, and also in non-English speaking countries, such as Austria, Italy, Netherlands and Slovenia (Biassutti et al 2015), Portugal (Mota 2015), and Brazil (Mateiro 2011). Separately, it has been reported that one of the main underlying reasons for this persistent need is that generalist initial teacher education programs customarily provide limited opportunities for sustained pre-service education in music (e.g., Erhlin & Wallerstedt 2014;Gifford 1993;Hennessy 2017;Koutsoupidou 2010;Welch & Henley, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…This need has been widely reported in research studies over many years, such as by Mills (1989), Hennessy (2000), Stunell (2006) and McCulloough (2006) in England, Stakelum (2008) in Ireland, Ballantyne (2007), Barton (2015) and Jeanneret (1997) in Australia, Bresler (1993) in the USA, and also in non-English speaking countries, such as Austria, Italy, Netherlands and Slovenia (Biassutti et al 2015), Portugal (Mota 2015), and Brazil (Mateiro 2011). Separately, it has been reported that one of the main underlying reasons for this persistent need is that generalist initial teacher education programs customarily provide limited opportunities for sustained pre-service education in music (e.g., Erhlin & Wallerstedt 2014;Gifford 1993;Hennessy 2017;Koutsoupidou 2010;Welch & Henley, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Research suggests that teachers of young children in community and school settings often have limited experience of music education, other than being able to draw on their own personal experience. Such experience, however, has its limitations, often leading to a reported “lack of confidence” in generalist music educators who are working in early childhood education and care (ECEC) settings and primary schools (Mills, 1989; Hennessy, 2000; McCullough, 2006; Seddon and Biasutti, 2008; Stakelum, 2008; Hallam et al, 2009; Stunell, 2010; Welch and Henley, 2014). Furthermore, this reported “lack of confidence” in the teaching of music tends not to be addressed sufficiently in Primary teachers' initial teacher education (pre-service) courses (e.g., Ballantyne and Packer, 2004; Ballantyne, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The special features of the learning community, such as, whether the community stimulates and fertilizes individual creative efforts and initiatives or ignores them (see Burnard, 2006), were essential in the process. Also elements such as the holistic curricula, the Finnish class-teachers’ possibilities for flexible classroom arrangements (both concerning subjects and overall management), ideal class sizes (max 24 students, enabling deep knowledge of the students), and the freedom to choose teaching methods were all supportive elements that allowed for songcrafting to take place: it is agreed that the framing circumstances and teacher’s interpretations of those circumstances contribute to their actions (Dogani, 2004; Stakelum, 2008; Young, 2006). In addition, the emotional and financial support provided by the principal, as well as a growing enthusiasm for song creation both in and outside school hours supported the building of a favorable medium wherein “communities of practice” were possible to be formed and modified.…”
Section: Discussionmentioning
confidence: 99%